2022
DOI: 10.1186/s12943-022-01646-1
|View full text |Cite
|
Sign up to set email alerts
|

A transcriptomic map of EGFR-induced epithelial-to-mesenchymal transition identifies prognostic and therapeutic targets for head and neck cancer

Abstract: Background Epidermal growth factor receptor (EGFR) is both a driver oncogene and a therapeutic target in advanced head and neck squamous cell carcinoma (HNSCC). However, response to EGFR treatment is inconsistent and lacks markers for treatment prediction. This study investigated EGFR-induced epithelial-to-mesenchymal transition (EMT) as a central parameter in tumor progression and identified novel prognostic and therapeutic targets, and a candidate predictive marker for EGFR therapy response. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 54 publications
(128 reference statements)
0
34
0
Order By: Relevance
“…DDIT4 (also known as REDD1) regulates p53/TP53 mediator apoptosis in response to DNA damage and regulates cell growth, proliferation and survival by inhibiting the activity of mammalian target of rapamycin complex 1 (mTORC1) [35][36][37] . Previous literature has revealed that DDIT4 expression was much higher in nasopharyngeal carcinoma (NPC) and HNSCC tissues than in adjacent tissues 38,39 . Zhao et al found that DDIT4 overexpression promotes the proliferation, migration, invasion and inhibits the apoptosis of NPC cells by partially activating the mTOR signaling pathway 39 .…”
Section: Discussionmentioning
confidence: 99%
“…DDIT4 (also known as REDD1) regulates p53/TP53 mediator apoptosis in response to DNA damage and regulates cell growth, proliferation and survival by inhibiting the activity of mammalian target of rapamycin complex 1 (mTORC1) [35][36][37] . Previous literature has revealed that DDIT4 expression was much higher in nasopharyngeal carcinoma (NPC) and HNSCC tissues than in adjacent tissues 38,39 . Zhao et al found that DDIT4 overexpression promotes the proliferation, migration, invasion and inhibits the apoptosis of NPC cells by partially activating the mTOR signaling pathway 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in HNSCC, transcriptomic signatures provide promising results with a potential therapeutic impact [ 46 ]. Here, we describe the RNA-seq results from three different HNSCC cell lines, according to their location (laryngeal, pharyngeal and metastatic pharyngeal cells).…”
Section: Discussionmentioning
confidence: 99%
“…Head and neck squamous cell carcinoma (HNSC) is a common malignant solid tumor that lacks effective treatment options, especially targeted therapies (Mody et al, 2021; Noronha et al, 2022). Although cumulative studies have revealed that human papillomavirus (HPV) infection, mammalian target of rapamycin signaling dysregulation, epidermal growth factor receptor amplification, and TP53 mutation are risk factors for HNSC and participate in tumor development, clinical trials based on these pan‐cancer oncogenic factors have not been very satisfactory (Nathan et al, 2022; Rodriguez et al, 2022; Schinke et al, 2022). Developing efficient therapeutic strategies for HNSC patients based on the concept of precision medicine remains a great challenge (Gu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%